2014
DOI: 10.4028/www.scientific.net/msf.803.179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Using NaOH and KOH Activated Fly Ash-Based Geopolymer on the Mechanical Properties

Abstract: Geopolymer synthesis has two main requirements to fulfil which are the source material that is rich in Silicon (Si) and Aluminum (Al) and alkali activator such as sodium/potassium hydroxide. Sodium hydroxide (NaOH) is widely used for the synthesis of geopolymer compared to potassium hydroxide (KOH) with addition of silicate solution for the purpose of increasing dissolution process. However, the comparison of using different activator in the absence of silicate solution for geopolymer synthesis is not well est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In this process, aluminosilicates are dissolved in highly-concentrated alkali hydroxide or silicate solution to form a structurally stable material composed of amorphous, interconnected Si–O–Al polymeric matrices via a combination of diffusion, coagulation and polycondensation ( Abdel-Gawwad and Abo-El-Enein, 2016 ; Rajamane et al., 2009 ). Geopolymers have excellent mechanical properties that are sometimes comparable to concrete or fired bricks when prepared under optimum conditions ( Abdul Rahim et al., 2015 ; Caballero et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, aluminosilicates are dissolved in highly-concentrated alkali hydroxide or silicate solution to form a structurally stable material composed of amorphous, interconnected Si–O–Al polymeric matrices via a combination of diffusion, coagulation and polycondensation ( Abdel-Gawwad and Abo-El-Enein, 2016 ; Rajamane et al., 2009 ). Geopolymers have excellent mechanical properties that are sometimes comparable to concrete or fired bricks when prepared under optimum conditions ( Abdul Rahim et al., 2015 ; Caballero et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, geopolymer treatment of a Pb-contaminated soil recorded a maximum UCS value of 4.35 MPa as compared to a UCS value of 1.2 MPa after treatment of silty clay [43,56]. On the other hand, a trend of high UCS values (65.28 MPa, 35.12 MPa, 48.55 MPa) was noted for geopolymer pastes when tested [31,60,63]. This shows that the geopolymer paste (alkali + pozzolan) on its own has the tendency to resist a lot more compressive load.…”
Section: The Past and Present: Soil Stabilization Using Geopolymersmentioning
confidence: 95%
“…Conversely, Abdul Rahim et al [31] compared the use of KOH and NaOH (8 M each) activated fly ash on the mechanical properties of geopolymer paste. It was observed that the highest compressive strength up 65.28 MPa was obtained using NaOH.…”
Section: The Past and Present: Soil Stabilization Using Geopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…122 Geopolymers derived from a K-based activator dissolve or degrade more readily compared with Na-based geopolymers whether foamed or not. 123,124126…”
Section: Alternative Binders To Portland Cementmentioning
confidence: 99%